PENGARUH KONSENTRASI PEREKAT TEPUNG TAPIOKA DAN PENAMBAHAN KAPUR DALAM PEMBUATAN BRIKET ARANG BERBAHAN BAKU PELEPAH AREN (Arenga pinnata) - Julham Prasetya Pane; Erwin Junary; Netti Herlina (Talenta Publisher (Universitas Sumatera Utara), 2015)
The demand of renewable energy resources has been increasing. Briquette is one of the alternative energy resource which can be produced from utilization of biomass. This research aims to obtain a briquette from sugar palm frond, to obtain the effect of adhesive concentration of cassava starch and addition of lime on the quality of briquettes. This research used the batch method. Research variabels are the adhesive concentration of cassava starch in 0%, 10%, 20% and 30% (w/w) and the addition of lime in 0%, 1%, 3% and 5% (w/w) based on the weight of char powder. General materials are sugar palm (Arenga pinnata) frond, cassava starch and lime, and the general tools are furnace, briquette printer, oven, moisture analyzer, universal testing machine and bomb calorimeter. Briquetting process was started with sugar palm fronds preparation then they’re carbonized at 350 oC for 2 hours. Product of carbonization as a charcoal which is added by a cassava starch adhesive and lime then they’re printed or shaped and dried to be a briquette. Analysis used is the proximate analysis of the test parameters moisture content, ash content, volatile combustion matter content, carbon content, calorific value and compressive strength. The best briquette is with adhesive concentration in 0% and addition of lime in 5% with the calorific value 6502,379 cal/g, 45,56% fixed carbon, 6,44% moisture, 18,00% ash, 30,00% volatile combustion matter and 59,141 kg/cm2 compressive strength.